An ameliorated two‐factor anonymous key exchange authentication protocol for mobile client‐server environment. (2nd October 2018) - Mahmood, Khalid; Naqvi, Husnain; Alzahrani, Bander A.; Mehmood, Zahid; Irshad, Azeem; Chaudhry, Shehzad Ashraf
Summary: Mobile communication is now an essential part of our day‐to‐day life due to expeditious progress in the industry of information technology. Prior to session key exchange with the corresponding server, a mobile user needs to be authenticated by that server in order to avail its services. Assorted authentication protocols are introduced so far, for authenticating the legitimate mobile users. Very recently, Lu et al introduced a two‐factor scheme for key exchange in the mobile client‐server environment. Lu et al declared that their introduced scheme is anonymous and robust for preventing potential attacks. However, we determined that the scheme of Lu et al is susceptible against server key reveal and smart card stolen attack. Moreover, it is also identified that their scheme is prone to traceability and anonymity violation attacks. Therefore, we proposed an improvement in order to increase the security and effectiveness. The immunity of the proposed protocol and correctness is tested, analyzed, and verified through formal proof of automated tool ProVerif and Burrows‐Abadi‐Needham logic, respectively. Moreover, the security and performance comparison also proved that the improved scheme is robust, efficient, and lightweight. Abstract : The proposed protocol is designed in a way to mitigate the security concerns with improved efficiency and robustness. The correctness and immunity against potential attacks of our protocol are verified through formal analysis using BAN logic and ProVerif, respectively. Moreover, performance and security analysis are also observed that revealed the security strength and performance efficiency of our protocol over the analogous protocols.